Disseminated paracoccidioidomycosis in a liver transplant patient - Valentim, Flavia de Oliveira [UNESP]; Tsutsui, Giuliane Minami [UNESP]; Fernandes Abbade, Luciana Patricia [UNESP]; Marques, Silvio Alencar [UNESP] (Elsevier B.V., 2021)
Paracoccidioidomycosis is an endemic systemic mycosis caused by Paracoccidioides brasiliensis complex and P. lutzii. It is a rare disease in non-HIV-induced immunosuppressed individuals. In organ transplant recipients, it is more frequently associated with immunosuppression after kidney transplantation. In a liver transplant patient, only one case has been published in the literature to date. The present report comprises the case of a 47-year-old female patient with disseminated skin lesions associated with signs and symptoms of systemic involvement of paracoccidioidomycosis that manifested one year after liver transplantation and under an immunosuppression regimen with tacrolimus and mycophenolate mofetil. (C) 2021 Sociedade Brasileira de Dermatologia. Published by Elsevier Espana, S.L.U.
Keywords: Dermatology; Liver; Paracoccidioidomycosis; Transplant